The Business Environment: A Global Perspective - Ian Worthington, Chris Britton and Ed Thompson (United Kingdom Pearson, 2018)
In a fast-paced and constantly changing world, it is more important than ever to have a sound appreciation of the context in which business organisations exist and operate. Now in its 8th edition, this best-selling textbook offers a comprehensive, yet accessible, introduction to the wide range of external influences that affect business operations and decisions in today's increasingly globalised world. "How do changing, and often unpredictable, economic or political conditions impact on business? " " " "How are business organisations affected by globalisation? " " " "What role do environmental responsibility and ethics have to play in business decisions?" Using well-known examples and case studies from a broad range of international organisations, this 8th edition of "The Business Environment" addresses these key questions and many more. It includes a chapter on the global context of business together with International Business in Action case studies, both of which clearly illustrate the global nature of today's world of business.
Keywords: Business; Management; (UGB-224) Business Management; (UGB-107) Introduction to Business Management; (BIN3038-N) Contemporary Issues in Business Management